Smart working and tele-conferences during the lockdown caused by COVID-19 bring new editorial guidelines - Mutti, Antonio (La Medicina del Lavoro, 2020)
At the time of writing, the COVID-19 pandemic is assuming a distinct shape as do healthcare systems around the world. Some countries resisted to the tsunami and are now re-opening their industrial and commercial activities while re-organizing to face a possible new wave. Others are still struggling not to be overwhelmed by the most significant public health challenge of the last century. In Italy, after a strict lockdown, almost all activities are re-opening, trying to navigate between Scylla (epidemics and its economic consequences) and Cariddi (economic recession and its adverse health effects) bearing in mind that there is collinearity between the circulation of money and spreading of the virus and that there is a serious risk of a vicious spiral which could affect the society. The prolonged lockdown deemed to prevent the spreading of the virus also reduced the circulation of money, and hence tax revenues, thus it will ultimately result in fewer finances available for social security and Public Health (3). The main political issue will then be the definition of a right point of equilibrium between risks and benefits, between action and precaution. As scientists, we are called to distinguish between what we know and what is unknown, between data and opinions, between facts and beliefs. [...]